The surgery outcomes of pediatric femoral shaft fractures and comparision of radiation risks - Yigit, Şeyhmus; Yıldırım, Azad (Acta Biomedica Atenei Parmensis, 2020)
Introduction: To show midterm results and compare the two methods utilized in pediatric femoral diaphysis fractures fixation and the risks of radiation. Methods: We conducted retrospective studies of 60 children and adolescent between the age of 6 to 16 years who were exposed to traumatic femoral shaft fractures and treated with methods of fixation titanyum elastic nail (EN), submuscular bridge plating (SBP) Twenty eight (18 males and 10 females) were treated with SBP (group 1), and 32 patients (18 males and 14 females) were treated with EN (group 2). Results: The mean age of the patients was 10,3 years. Duration of follow-up was 29.8 months. Mean union time was 7,4 weeks (range, 6-10 weeks). Operative time was on average 60.6 minutes. Considering Flynn’s criteria, the results of treatment was excellent in 50, good in 4 and poor in 6 cases. Conclusions: In the surgical treatment of pediatric femoral shaft fractures, fixation techniques such as submuscular bridge platingand elastic nails were found to have similar fracture healing and complication rates. An orthopaedic surgeon must protect himself, his personnel and the patient from radiation exposure. Open reduction internal plate fixation can be chosen as an alternative treatment for children who do not cause radiation exposure to the femoral fracture.